ISLAM GARASSIK: DOUBLE MINORITY STRUGGLES AND SURVIVAL STRATEGIES IN A MULTICULTURAL SOCIETY - Hasyim, Baso; Langaji, Abbas; Barsihannor, Barsihannor; Hasanuddin, Muhammad Irfan; Kamil, M. Ilham (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
This research aims to delves into the survival strategies of Islam Garassik adherents within the diverse context of Tana Toraja society in South Sulawesi. Islam Garassik is not only a subculture in Torajan culture, but also a double minority group. They are not only a minority within the mainstream of Torajan culture but also within the Islamic community itself. This qualitative research employs an interpretative phenomenological approach within Tana Toraja Regency, specifically in Gandangbatu Sillanan Sub-district. Data were collected through observation, in-depth interviews, and documentation. The research results show that Islam Garassik is an emerging form of Muslim religiosity in Tana Toraja, South Sulawesi, particularly in Lembang Garassik and Gandangbatu Sillanan sub-districts. This phenomenon combines Islamic teachings with local values, showing Islamic syncretism that is friendly to local traditions. Garassik Islam was born out of interactions with Bugis merchants in Mebali, a traditional market, and was influenced by the long and intense history of struggle between religious and cultural institutions in South Sulawesi. As a multiple minority group, Garassik Islam adherents face social exclusion that pushes them to defend their existential identity and values, including religious understanding and ritual practices. In their defense strategy, they negotiate their identity by integrating religious values and traditions, using Sufistic narratives, and interacting with other Muslim groups. This strategy allows them to maintain their religious identity and cultural diversity, establish harmonious relations with the surrounding community, and provide space for the growth of Islam in the rich cultural context of Tana Toraja.